MiR-485-3p and miR-485-5p suppress breast cancer cell metastasis by inhibiting PGC-1α expression - Lou, C (Cell Death Dis, 2016)
Breast cancer is the worldwide leading cause of cancer mortality in women. The majority of deaths from breast cancer arise from metastasis of local tumors. Cancer cells support their rapid proliferation by diverting metabolites into anabolic pathways, but during cancer metastasis, the proliferative program of invasive cancer cells is suspended for a migratory phenotype. In this study, we demonstrated that both mature forms of miRNA-485, miR-485-3p and miR-485-5p were involved in regulating mitochondrial respiration, cell migration and cell invasion in breast cancer cells by directly targeting and inhibiting the expression of PGC-1α. Specifically, the expression levels of both miR-485-3p and miR-485-5p were decreased in breast cancer tissues. Overexpression of miR-485-3p and miR-485-5p suppressed mitochondrial respiration and potential for cell migration and invasion in vitro, and also inhibited spontaneous metastasis of breast cancer cells in vivo. The suppression of mitochondrial respiration and cell invasion could be partially relieved by restoration of PGC-1α expression.